2020
DOI: 10.1212/wnl.0000000000008977
|View full text |Cite
|
Sign up to set email alerts
|

Preserved single muscle fiber specific force in facioscapulohumeral muscular dystrophy

Abstract: ObjectiveTo investigate single muscle fiber contractile performance in muscle biopsies from patients with facioscapulohumeral muscular dystrophy (FSHD), one of the most common hereditary muscle disorders.MethodsWe collected 50 muscle biopsies (26 vastus lateralis, 24 tibialis anterior) from 14 patients with genetically confirmed FSHD and 12 healthy controls. Single muscle fibers (n = 547) were isolated for contractile measurements. Titin content and titin phosphorylation were examined in vastus lateralis muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We have previously investigated sarcomeric function in muscle fibers isolated from the same biopsies that were used in this study, and showed maximum and specific force generation are preserved in FSHD single muscle fibers. 31 A limitation from this study is its small sample size and the use of conception and design of the study and obtained funding. All authors provided critical input for interpretation of the data and approved the final version of the manuscript.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously investigated sarcomeric function in muscle fibers isolated from the same biopsies that were used in this study, and showed maximum and specific force generation are preserved in FSHD single muscle fibers. 31 A limitation from this study is its small sample size and the use of conception and design of the study and obtained funding. All authors provided critical input for interpretation of the data and approved the final version of the manuscript.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously investigated sarcomeric function in muscle fibers isolated from the same biopsies that were used in this study, and showed maximum and specific force generation are preserved in FSHD single muscle fibers. 31 A limitation from this study is its small sample size and the use of axial muscle MRI images at a single level, to determine quadriceps cross-sectional area. In healthy subjects without muscle disease, quadriceps cross-sectional area at this level correlates well with quadriceps muscle volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is corroborated by an increased predicted muscle weakness experienced by patients with FSHD. A recent study by Lassche et al (2020) hypothesized that muscle weakness in FSHD is not caused by alterations in sarcomeric contractility, or excitation-contraction coupling (Vandebrouck et al 2002), but is due to DUX4-induced toxicity and consequential loss of muscle fibers or to an unknown impaired metabolic cause. In addition, the patients' endurance time was significantly longer than in HC, suggesting an increased resistance to the development of fatigue (Fig.…”
Section: Muscle Weakness Strength and Endurance Timementioning
confidence: 99%
“…The primary mediator of FSHD pathology is thought to be the expression of DUX4, a gene epigenetically repressed in most somatic tissues located in each unit of the D4Z4 repeat array (Lemmers et al 2010 ). In patients with FSHD, inadequate DUX4 protein expression in skeletal muscle is favored by D4Z4 chromatin relaxation (Lassche et al 2020 ). Clinically, FSHD is characterized by slowly progressive weakness of the muscles of the face, shoulder, and upper arm.…”
Section: Introductionmentioning
confidence: 99%